The effect of the athletes` origin and type of impairment on participation and the likelihood of winning a medal in the Paralympic Games - Severin, A. C.; Kinderen, A.; Baumgart, Kathrin (American Journal of Physical Medicine & Rehabilitation, 2025)
Objective This study investigated whether the origin (acquired or congenital) and type of impairment affect the participation and likelihood of winning a medal in different sports at the Paralympic Games.